Uma análise dos impactos macroeconômicos da política de transferência de renda no Brasil no período de 1995 a 2014 : uma interpretação pós-keynesiana - Coimbra, Reurison dos Santos (2018)
The present dissertation aims to analyze income transfers, specifically the “Bolsa Família” Program and the “Benefício de Prestação Continuada”, from 1995 to 2014, based on a Post Keynesian analysis. For this, an analysis was made of the fiscal policy pursued during this period, an analysis necessary to understand the conjuncture in which such programs were implemented. During this period there was a sharp fall in income inequality as a result, in part, of these transfers. The effects of these policies on income inequality and poverty, as well as the impact on the level of activityare analyzed. The impact assessment is carried out empirically through the technique known as Autoregressive Model (VAR).